Social Cohesion in Community Participation in The Ruwat Air Tradition in Penanggal Village, Candipuro District, Lumajang Regenc - Noviawati Syah Putri; Rizki Agung Novariyanto (Historia Madania: Jurnal Ilmu Sejarah, 2026)
This study aims to describe the forms of social cohesion in community participation in the Ruwat Air Tradition in Penanggal Village, Candipuro District, Lumajang Regency. The method used was descriptive qualitative with an ethnographic approach. The data were collected through observation, in-depth interviews with key informants such as the tradition's caretaker, village elders, village heads, and participating residents, as well as field documentation over eleven days in January 2025. The results indicate that community participation in the Ruwat Air Tradition is carried out through the active involvement of all levels of society, from children to village elders, in every series of the process, such as the procession of the mountain-shaped arrangement of agricultural produce (kirab gunungan hasil bumi), communal prayers, traditional dances, the face-washing ritual, kembul bujana (a communal feast), and the wayang ruwat (ritual puppet performance). This participation reflects the formation of strong social cohesion, marked by a growing sense of togetherness, mutual cooperation, solidarity, and collective responsibility among residents regardless of background or social status. The Ruwat Air tradition not only serves as a spiritual ritual and preserves local culture, but also serves as a means of community unification, strengthening the identity and social solidarity of Penanggal Village amidst the tide of modernization. Keywords: social cohesion, community participation, ruwat air, solidarity, local tradition